The Effect of Sex, Sport Participation, and Concussion History on Baseline Concussion Balance Test Performance in Division-I Collegiate Athletes. (4th January 2022) - Quintana, Carolina; Morelli, Nathan; Andrews, Morgan L.; Kelly, Madison; Heebner, Nicholas; Hoch, Matthew
Abstract : Objective: Explore the effect of baseline characteristics such as sex, sport, and concussion history on the Concussion Balance Test (COBALT) performance in collegiate athletes. Background: The COBALT is a recently developed clinical balance assessment specifically for athletic populations following concussion. The task conditions of the COBALT are designed to challenge sensory integration and reweighting processing underlying postural control. It has been documented that balance performance is influenced by factors such as sex and sport in collegiate athletes. Design/Methods: One-hundred twenty seven collegiate athletes (77 male, 50 female; age: 19.81 ± 1.39; height: 68.77 ± 5.57 in; mass: 80.98 ± 26.15 kg), who participated in Division-I football, soccer, or cheerleading were included. Participants completed the 4 baseline conditions (Condition 3, 4, 7, 8) of the COBALT. Condition 3 (C3) included a side-to-side headshake with eyes closed. For Condition 4 (C4) the participant stood with hands clasped, elbows extended, and thumbs up while rotating their trunk side-to-side, visually focusing on their thumbs. Conditions 7 (C7) and 8 (C8) repeated C3 and C4 on a foam surface. Two 20-second trials of each condition were completed on a forceplate and the mean angular sway velocity (°/s) were calculated and number of errors were counted. ANOVAs and ANCOVAs were used to assess the potential effects on COBALT performance. Results: There were no significant differences in postural sway for any COBALT condition based on sex ( p > 0.05). Females demonstrated more errors than males on C7 ( p < 0.001). Cheerleaders had more balance errors compared to football athletes for C3 and C7 ( p < 0.05) and soccer athletes for C7 ( p < 0.05). Concussion history did not have an effect on COBALT performance ( p > 0.05). Conclusions: Understanding factors that may influence COBALT performance at baseline may enhance concussion evaluation in collegiate athletes with suspected balance deficits following concussion. While concussion history had no effect, sex and sports participation may influence performance and should be considered when interpreting COBALT results post-concussion.